Adjuvant radiotherapy did not increase the risk of coronary heart disease in patients with non-metastatic breast cancer. Issue 4 (19th May 2022) - Sun, Li-Min; Sun, Sean; Lin, Cheng-Li; Kao, Chia-Hung
ABSTRACT: Objective: Adjuvant radiotherapy (RT) in patients with breast cancer can adversely cause the heart to receive some radiation doses, which may lead to cardiovascular diseases. The results of previous research regarding this issue are not consistent. Therefore, we conducted a nationwide population-based study in Taiwan to evaluate whether adjuvant RT for breast cancer patients increased the risk of developing coronary heart disease (CHD). Methods: This retrospective cohort study examined data from the National Health Insurance Research Database, Registry for Catastrophic Illness Patients, and Taiwan Cancer Registry Database. We identified 83, 733 patients with breast cancer between 1 January 2000 and 31 December 2017. Individuals without breast cancer from the general population were frequency-matched by age and index year with individuals with breast cancer. Participants were followed until the occurrence of a CHD event, the end of follow-up, or patient record removal due to death or withdrawal from the NHI. A Cox proportional hazards regression analysis was conducted to compare the risk of CHD in breast cancer patients with that in patients in the comparison cohort. Results: Compared to breast cancer patients without RT, those who underwent RT had a similar risk of subsequently developing CHD (adjusted hazard ratio, 0.94; 95% confidence interval, 0.87–1.02). Similar results were observed in a subgroup of patients with left-sided breast cancer. However, among patients who received adjuvant RT, those with left-sided breast cancer had a significantly higher risk of CHD than did those with right-sided breast cancer (adjusted hazard ratio, 1.17; 95% confidence interval, 1.04–1.30). Patients who received RT in 2010 or later had a significantly lower risk of CHD compared with those who received RT before 2010 (adjusted hazard ratio, 0.64; 95% confidence interval, 0.45–0.91). Higher prescribed doses of RT to the left-sided breast did not correspond to a higher risk of CHD. Conclusion: This large, nationwide cohort study suggests that adjuvant RT in patients with breast cancer did not increase the risk of CHD.